THE IMPACT OF COMPANY DECISIONS AND ACTIVITIES ON THE ENVIRONMENT IN TERMS OF LAW - Karina Loanardo Susanto (Jurnal Scientia, 2023)
This study aims to determine the implementation of ISO 26000 in Indonesia and also to determine the relationship between the impact of company decisions and activities and CSR. It can be seen that Indonesia itself is still trying to attract investors and create jobs and better economic growth. one of the industries that exist in Indonesia and which is no less dead are companies/industries that have direct contact with Natural Resources (SDA). Because as is known that Indonesia has a very large natural resource potential. Seeing the importance of natural resources as explained above, countries are starting to pay attention to the surrounding environment or pay attention to social aspects. Then, the demand to pay attention to the social aspects of the company appears as a reflection of corporate responsibility (social responsibility) to all of its main stakeholders, which consist of employees, buyers, investors/customers, government, community and environmental sustainability for future generations. Therefore, Indonesia also regulates related to CSR itself which is spread over several rules. As with other regulations, CSR is also experiencing developments. For example: CSR version ISO 26000. The research method that will be used in this study is normative juridical. Where, library law research is carried out by examining library materials or mere secondary data, namely: through journals, books, the internet and statutory regulations. The study results show that the lack of enforcement and supervision of company decisions and activities causes damage to the surrounding environment. Even though CSR has been carried out, if CSR is not on target, it cannot be categorized as "social responsibility".